Changes in peripheral T-lymphocyte subsets and serum cytokines in patients with systemic sclerosis - Guo, Rong-Hong; Cheng, Hao; Zhang, Xiao-Ying; Yu, Zhen; Wang, Guang-Hui; Hao, Shu-Ya; Gao, Xiao-Peng; Wen, Hong-Yan (Frontiers in Pharmacology, 2022)
Objective. T cells represent a predominant cell type in autoimmune disease. However, their exact roles are not fully clear in systemic sclerosis (SSc). This study aimed to mainly investigate the alteration in the absolute numbers of T-lymphocyte subsets and the serum levels of cytokines in SSc patients. Methods. A total of 76 patients with SSc and 76 age- and sex-matched healthy controls (HCs) were enrolled. The levels of circulating T cell subsets and serum cytokines were measured by flow cytometry. T cell subsets or serum cytokines correlations with disease activity and organ involvement were analyzed. Results. The absolute numbers of Th2 and Treg cells in SSc patients were lower than those in HCs (p<0.05), resulting in the ratios of Th1/Th2 [25.01(12.24, 38.61) vs 11.64(6.38, 20.34)] and Th17/Treg [0.42(0.17, 0.66) vs 0.17(0.13, 0.29)] were increased significantly (p<0.001). The absolute numbers of total T, Th, and Treg cells were negatively correlated with CRP (r=-0.406, p=0.002; r=-0.263, p<0.05; r=-0.367 p<0.01). The serum levels of IL-2, SIL-2R, IL-6, IL-10, INF-γ, and TNF-α were significantly higher than those in HCs (p<0.001). Increasing IL-2 in the wake of the augment of ESR (r=0.671, p=0.004), so did IL-6 (r=0.378, p<0.05). The ratio of Th17/Treg in SSc-ILD patients had lower levels than that in other patients [0.35(0.14, 0.53) vs 0.64(0.26, 0.93) p=0.028]; Treg cells were lessened in patients with Raynaud's phenomenon relative to controls [3.00(2.41, 4.28) vs 3.55(2.86, 4.53) p<0.05]. The levels of IL-2, IL-10 and INF-γ [3.32(1.05,11.73) vs 2.32(0.44,6.45), p=0.045], [8.08(3.63, 355,77) vs 4.89(0.78, 21.44), p=0.02], [6.31(2.66, 44.03) vs 4.03(0.22, 16.96), p=0.009] were elevated in patients with arthralgia, while the level of Th17 was decreased [0.62(0.20,2.16) vs 1.26(0.22,10.93), p=0.026]. ROC curve analysis yielded an optimal cut-off IL-2, IL-10, and INF-γ levels of 2.67, 5.93, and 5.32 pg/mL for the presence of arthralgia. Conclusion. We exhibited abnormalities in T subsets and the production of their cytokines in SSc, as compared with those in HCs. This may allow the pathogenesis of SSc and the development of novel therapeutic interventions aimed at targeting these cells and the cytokines they produce.